Serial murderers and their victims - Hickey, Eric W. (Cengage Learning, 2016)
Introduction -- Cultural development of monsters, demons, and evil -- Psychopathology and biogenics of serial murderers -- Social construction of serial murder -- Sexual predators, criminal paraphilia, and murder -- Healthcare killers -- The male serial murderer -- Team killers -- The female serial murderer -- Victims of serial murder -- Serial murder: a global perspective -- Responding to serial murderers